The Effect Of Papaya Leaf Extract (Carica Papaya L) On Methemoglobin Percentage And The Number Of Erythrocyte Cells In Wistar Strain White Male Rats Induced With Sodium Nitrite - Jessica Alda; Diah Hermayanti; Hawin Nurdiana (Saintika Medika, 2021)
Sodium nitrite is widely used nowadays, especially in the meat processing industry. In the case of an overdose, it can cause poisoning, which causes the oxidation of the iron component in the hemoglobin of erythrocytes to methemoglobin, thereby damaging cell membranes and hemolytic. Papaya leaves contain antioxidants that can inhibit the oxidation of iron components in hemoglobin. To determine the effect of papaya leaf extract on methemoglobin levels and the number of erythrocytes in white male Wistar rats strain induced with sodium nitrite. True experimental research design using post test only control group design. The object of this study was male white rats (Rattus novergicuswistar strain) induced intraperitoneally with sodium nitrite. The study was divided into a negative control group, a positive control group, a treatment group with a dose of papaya leaf extract PI (0.7 ml/200 g BW), PII (1.4 ml/200 g BW), PIII (2.8 ml/200 g BW). BB). Kruskal-Wallis test, methemoglobin levels sig. 0.001 (p<0.05). One wayannova test, erythrocyte cell count sig. 0.021 (p<0.05). Post Hoc test there was a significant difference between the negative control group and the positive control group on all variables, not different from the PII group for methemoglobin levels, not significantly different from the three treatment groups for the number of erythrocytes. Papaya leaf extract contains antioxidants that can inhibit the formation of methemoglobin, and maintain the number of erythrocytes. Papaya leaf extract can inhibit the formation of methemoglobin, maintain the number of erythrocytes in male Wistar strain rats induced with sodium nitrite.